Single-cell transcriptomic analyses of cardiac immune cells reveal that Rel-driven CD72-positive macrophages induce cardiomyocyte injury. Issue 5 (8th June 2021) - Ni, Shi-Hao; Xu, Jin-Dong; Sun, Shu-Ning; Li, Yue; Zhou, Zheng; Li, Huan; Liu, Xin; Deng, Jian-Ping; Huang, Yu-Sheng; Chen, Zi-Xin; Feng, Wen-Jun; Wang, Jia-Jia; et al.
Abstract: Aims : The goal of our study was to investigate the heterogeneity of cardiac macrophages (CMφs) in mice with transverse aortic constriction (TAC) via single-cell sequencing and identify a subset of macrophages associated with heart injury. Methods and results : We selected all CMφs from CD45+ cells using single-cell mRNA sequencing data. Through dimension reduction, clustering, and enrichment analyses, CD72 hi CMφs were identified as a subset of pro-inflammatory macrophages. The pseudo-time trajectory and ChIP-Seq analyses identified Rel as the key transcription factor that induces CD72 hi CMφ differentiation. Rel KD and Rel−/− bone marrow chimaera mice subjected to TAC showed features of mitigated cardiac injury, including decreased levels of cytokines and ROS, which prohibited cardiomyocyte death. The transfer of adoptive Rel-overexpressing monocytes and CD72 hi CMφ injection directly aggravated heart injury in the TAC model. The CD72 hi macrophages also exerted pro-inflammatory and cardiac injury effects associated with myocardial infarction. In humans, patients with heart failure exhibit increased CD72 hi CMφ levels following dilated cardiomyopathy and ischaemic cardiomyopathy. Conclusion : Bone marrow-derived, Rel-mediated CD72 hi macrophages play a pro-inflammatory role, induce cardiac injury and, thus, may serve as a therapeutic target for multiple cardiovascular diseases. Graphical Abstract: